Applying of Social Return on Investment (SROI): A Practical Review to Financial Social Value and Benefits - Munthe, Al Akhyar; Nazaruddin; Sembiring, Meilita Tryana (Jurnal Sistem Teknik Industri, 2024)
The objective of the study is to analyze a Social Return on Investment method for companies. Data were collected from scientific publications from 2007 to 2022 and selected based on previous studies. The main principle is to explore, review, and formulate the benefits and contributions of all research, as well as the application of various types of SROI. The methodology resulted in 13 articles that identified the social values and benefits of SROI over the last decade. The results obtained in this paper were reviewed using tables for advanced analysis. Additionally, this study presents qualitative results and investigates methodical publications that have had a significant impact on the company.